2013
DOI: 10.1259/dmfr/91866873
|View full text |Cite
|
Sign up to set email alerts
|

Dental cone beam CT image quality possibly reduced by patient movement

Abstract: Patient artefacts in dental cone beam CT scans can happen for various reasons. These range from artefacts from metal restorations to movement. An audit was carried out in the Glasgow Dental Hospital analysing how many scans showed signs of "motion artefact", and then to assess if there was any correlation between patient age and movement artefacts. Specific age demographics were then analysed to see if these cohorts were at a higher risk of "movement artefacts". Dentomaxillofacial Radiology ( Keywords: hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 2 publications
4
37
1
3
Order By: Relevance
“…12 It is well known that patient motion artefacts influence the obtainable resolution of the final CBCT reconstructed image, rather than the resolution of the unit's flat panel detector. 12 Very few studies 13,14,16 in the literature have assessed the image quality and visual characteristics of CBCT examination for the presence of artefacts supposedly related to patient movement. These studies reported that between 4.5% and 41.5% of CBCT examinations show artefacts suggestive of patient movement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 It is well known that patient motion artefacts influence the obtainable resolution of the final CBCT reconstructed image, rather than the resolution of the unit's flat panel detector. 12 Very few studies 13,14,16 in the literature have assessed the image quality and visual characteristics of CBCT examination for the presence of artefacts supposedly related to patient movement. These studies reported that between 4.5% and 41.5% of CBCT examinations show artefacts suggestive of patient movement.…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported that between 4.5% and 41.5% of CBCT examinations show artefacts suggestive of patient movement. 13,14,16 But, although some studies 7,8 report on the possible impact of motion artefacts on image quality, knowledge of which types and magnitudes of movements may considerably hamper the diagnostic outcome of a CBCT examination is still a key question. 8 Moreover, it is unclear whether observed artefacts in some studies 13,14,16 were in fact due to patient motion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Donaldson ve arkadaşları 17 KIBT görüntülerinde hareket artefaktı oranını ve bu artefaklara bağlı tanısal yetersizlik nedeniyle yapılan çekim tekrarlarını belirlemek amacıyla yaptıkları retrospektif çalışmada; ilk çekimlerin % 95,5'inde hareket artefaktı görülmediğini bildirmişlerdir. Tüm çekimlerin % 99,5'inin çekim tekrarı gerektirmeyecek tanısal doğruluğa sahip olduğunu bildirmişlerdir.…”
Section: Hasta İle İlgi̇li̇ Artefaktlarunclassified
“…16 yaş altı ve 65 yaş üzeri hastalarda çekim sırasında oluşan hareket artefaktlarında artış görüldüğünü belirtmişlerdir. 17 Spin-Neto ve arkadaşları 16 tam dişli bir insan kafatasına değişik hareketler vererek, KIBT ile görüntü elde ettikleri çalışmalarında; bütün hareket artefaktları arasında (çizgi şeklinde, çift konturlu, keskin olmayan (netsizlik) ve halka şeklinde artefaktlar), en fazla çizgi şeklinde artefaktların görüldüğünü bildirmişlerdir. Mental foramen, infraorbital foramen ve supraorbital foramen seviyelerinde oluşan artefaklar dikkate alındığında en fazla artefaktın mental foramen seviyesinde görüldüğünü belirtmişlerdir.…”
Section: Hasta İle İlgi̇li̇ Artefaktlarunclassified